Guide wire-assisted cannulation versus conventional contrast to prevent pancreatitis. A systematic review and meta-analysis based on randomized control trials - De Moura, Eduardo T.H. (2017)
Objective: Through this systematic review and meta-analysis, we aim to clarify the differences between these two techniques, thus improving primary success cannulation and reducing complications during endoscopic retrograde cholangiopancreatography, primarily pancreatitis. Methods: A comprehensive search was conducted to search for data available up until June2015from the most important databases available in the health field: EMBASE, MEDLINE (via PubMed), Cochrane, LILACS and CENTRAL (via BVS), SCOPUS, the CAPES database (Brazil), and gray literature. Results: Nine randomized clinical trialsincluding2583 people were selected from20,198 studies for meta-analysis. Choledocholithiasis had been diagnosed in mostly (63.8%) of the patients, who were aged an average of 63.15 years. In those patients treated using the guide wire-assisted cannulation technique, provided a significantly lower instance of pancreatitis (RD=0.03; 95% CI: 0.01-0.05; I2= 45%) and greater primary success cannulation (RD=0.07; 95% CI: 0.03-0.12; I2=12%) than conventional contrast cannulation. Conclusions: The guide wire-assisted technique, when compared to the conventional contrast technique, reduces the risk of pancreatitis and increases primary success cannulation rate. Thus, guide wire-assisted cannulation appears to be the most appropriate first-line cannulation technique.